Bottom-Up Touristification in Yogyakarta after Pandemic Covid-19 - Shinta Permana Putri (Media Wisata, 2024)
This research was conducted to identify the bottom-up touristification phenomenon that occurred in the city of Yogyakarta  after the Covid-19 pandemic. This research is a qualitative research. Data was collected through a process of observation and secondary data survey. The analysis techniques used are spatial analysis and also qualitative descriptive. The results of this research show that the touristification phenomenon occurring in Yogyakarta can be identified through changes in function and environment both visually and non-visually as well as changes in mobility aspects. Changes in function and environment can be seen both visually from the development of spatial concentration and the spread of tourists, changing the function of the area into a tourist area, and also the increase in facilities for tourists. Changes in function and environment non-visually can be seen from the development and distribution of accommodation which increases community profits and encourages tourists to travel to places that were not originally tourist attractions. Changes in the mobility aspect can be seen from changes of roads function as part of attractions which can then encourage environmentally friendly habits in the community. In the end, this touristifcation phenomenon can indirectly help tourism activities to adapt after the Covid-19 pandemic. The government is expected to increase its support to ensure that this touristification phenomenon can run according to the carrying capacity and capacity of tourism in Yogyakarta city.